Graphene Oxide–Polyphenylsulfone Nanocomposite Beads for Paracetamol Removal from Aqueous Solution - Mansour Alhoshan; Arun Kumar Shukla; Javed Alam; Ali Awadh Hamid (Membranes, 2023)
This study introduces a promising and practical method for the removal of paracetamol from aqueous environments, employing graphene oxide–polymer nanocomposite beads. The approach involves the utilization of a straightforward and facile phase inversion method, offering a convenient and efficient one-step process for the creation of adsorbent beads by integrating polymers and graphene oxide (GO). The synthesized nanocomposite beads are tailored for the removal of paracetamol from simulated wastewater in batch systems. Extensive characterization techniques including XPS, FTIR, SEM, TGA, and zeta potential analysis are employed to scrutinize the chemical properties and structural attributes of the prepared beads. The investigation explores the impact of critical parameters such as adsorbent dosage, adsorption duration, initial paracetamol concentration, and solution pH on the adsorption process. These nanocomposite beads exhibit an exceptional paracetamol removal efficiency, achieving up to 99% removal. This research not only contributes to the advancement of efficient and sustainable adsorbent materials for pollutant removal but also underscores their potential for environmentally friendly and cost-effective solutions in the domain of wastewater treatment.